Household Water Quality, Sources, Storage and Treatment in Korangi and Landhi Town of Karachi - Mobin, Rimsha; Urooj , Huma (Nurture, 2015)
Water is essential human need in world there is a lack of awareness regarding water sources, storage, treatment and the quality of drinking water. This study aimed to study and compare the quality sources, storage and treatment of drinking water in Korangi and Landhi towns in Karachi. A random 50 sample 25 from each town the data was obtained. The tools used to collect data through observation cum questionnaire through survey method. The research concludes that both Korangi and Landhi Town has no difference in their quality of household water. But they have some difference in storage, sources and treatment.